The Italian wage curve reloaded: Does occupation matter? - Gianluca Gucciardi (Kiel Institute for the World Economy (IfW), 2014)
This paper provides some evidence on the existence of the wage curve - the negative relationship between individual wages and the local unemployment rate - within a number of occupations. It exploits the Bank of Italy's Household Survey and draws data from 1977 to 2008. An occupation-level wage curve exists for all the employees, while it holds only for a sub-set of the self-employed. In particular, the wage curve has an elasticity of approximately -0.05 for the blue-collars, an elasticity of -0.1 for the employees and of approximately -0.2 for the executives. This suggests that professional labor markets may have different levels of flexibility, also within the same country. In particular, the professional categories with higher (lower) levels of negative elasticity belong to more (less) flexible labor markets.
Keywords: J31; J64; E24; 330; wage curve; occupation; unemployment; Italian regions